A description of shock attenuation for children running - Mercer, J. A.; Dufek, J. S.; Mangus, B. C.; Rubley, M. D.; Bhanot, K.; Aldridge, J. M. (Journal of Athletic Training, 2010)
Context: A growing number of children are participating in organized sport activities, resulting in a concomitant increase in lower extremity injuries. Little is known about the impact generated when children are running or how this impact is attenuated in child runners.